Adherence to antiretroviral therapy and determining factors in adults living with HIV receiving services at public health facilities amidst the COVID-19 crisis in Bahir Dar city, Northwest Ethiopia - Gela, Chalachew Dessie; Tsegaye, Gebiyaw Wudie; Shibesh, Belayneh Fentahun (Frontiers in Public Health, 2024)
Abstract Background: The COVID-19 pandemic has presented new challenges to adhering to ART, and its influence on adherence and related factors has not been thoroughly studied. This study examines ART adherence and its associated factors during the COVID-19 pandemic. Methods: A cross-sectional study was conducted on HIV-positive individuals receiving care and treatment in public health institutions. A total of 612 participants were selected using a multi-stage sampling procedure. Data were collected through interviewer-administered questionnaires and chart reviews. We used Epi-data for data entry and Stata for data analysis. Results: Good adherence to antiretroviral therapy in this study was 76.5% (95% CI: 72.9, 79.7). Divorced marital status (AOR=0.45,95%CI:0.22,0.90), regular follow-up (AOR=3.01,95%CI:1.81,5.01), adherence counseling and information in the context of COVID-19 pandemic (AOR=2.57,95%CI:1.63,4.08), and knowledge about ART (AOR=1.81,95%CI:1.11,2.94) were significantly associated with adherence to antiretroviral therapy. Conclusion: The observed adherence rate in this study was lower than the World Health Organization recommendation and previous studies. The study highlighted the importance of addressing adherence to ART among HIV-positive adults during the COVID-19 pandemic and other upcoming emerging and reemerging outbreaks. Strategies to improve adherence should consider factors such as marital status, regular follow-up, provision of counseling and information, and enhancing knowledge about ART.